2021
DOI: 10.4269/ajtmh.21-0613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Heating on Bioefficacy of Deltamethrin-Coated Long-Lasting Insecticidal Nets

Abstract: The authors recently reported that long-lasting insecticidal nets (LLINs) distributed in Papua New Guinea (PNG) between 2013 and 2019, exhibited severely diminished efficacy to knock down and kill susceptible Anopheles mosquitoes. This coincided with a rise in malaria observed in PNG since 2015. Here, the authors show that LLIN bioefficacy is increased by heating LLINs prior to WHO cone bioassays. Unused LLINs with low bioefficacy, delivered to PNG in 2019, were heated to 120°C for 5 minutes. Cone bioassays we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Also, older nets that had been stored for much longer and exhibited 100% 24h mosquito kill rate had, on average, slightly lower insecticide content which we attributed to the expected natural decay over many years of storage [4]. In addition, we showed that short-term heating of the LLINs in question increased their potency to kill mosquitoes (rather than to decrease it), which can be explained by heat-facilitated migration of the insecticide from inside the LLINs' polymer coating to the net surface [7,8]. It was also suspected that the mosquito strain that we had used (a fully pyrethroid susceptible strain of Anopheles farauti) or technicalities related to conducting WHO cone bioassays at the PNG Institute of Medical Research were responsible for the observed inferior LLIN performance.…”
Section: Introductionmentioning
confidence: 67%
“…Also, older nets that had been stored for much longer and exhibited 100% 24h mosquito kill rate had, on average, slightly lower insecticide content which we attributed to the expected natural decay over many years of storage [4]. In addition, we showed that short-term heating of the LLINs in question increased their potency to kill mosquitoes (rather than to decrease it), which can be explained by heat-facilitated migration of the insecticide from inside the LLINs' polymer coating to the net surface [7,8]. It was also suspected that the mosquito strain that we had used (a fully pyrethroid susceptible strain of Anopheles farauti) or technicalities related to conducting WHO cone bioassays at the PNG Institute of Medical Research were responsible for the observed inferior LLIN performance.…”
Section: Introductionmentioning
confidence: 67%
“…Also, older nets that had been stored for much longer and exhibited 100% kill rate had, on average, slightly lower insecticide content which we attributed to natural decay over many years of storage 7 . In addition, we showed that short-term heating of the LLINs in question increased their potency to kill mosquitoes (rather than to decrease it), which we attributed to a heat-facilitated migration of the insecticide from inside the coating to the net surface 8,9 .…”
Section: Main Textmentioning
confidence: 83%
“…Unused PermaNet ® 2.0 nets manufactured in 2012 were obtained from the Madang Provincial Health Authority. Two groups of PermaNet ® 2.0 samples were included as they exhibit substantially different bioefficacy as shown in previous studies [ 12 , 26 ]. More details about the individual LLIN samples are provided in Additional File 1 .…”
Section: Methodsmentioning
confidence: 99%